Implikatur Tuturan dalam Meme Pandemi Covid-19 - Puspitasari, Peni (FKIP Universitas Wisnuwardhana, 2020)
The purpose of this study was to determine the implications of speech in the COVID-19 pandemic memes studied in the community, the research method used was a descriptive qualitative method by taking the research subject in the form of COVID-19 pandemic memes seen on the internet, the results of the study were descriptions of the analysis of the implications of speech in a COVID-19 pandemic meme.